(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article outlines the theoretical foundations of labor organization in industrial enterprises in the context of digitalization of the economy, analyzes the state and trends of labor organization in industrial enterprises, and makes proposals for improving the organization of labor in industrial enterprises in the context of digitalization of the economy. conditions of digitalization of the economy.